SENTIMENT ANALYSIS PUBLIC PERSPECTION FROM ARTEMIS 2 MISSION USING RECURRENT NEURAL NETWORK METHODS - Muhammad Agym; Mayatopani, Hendra (Jurnal Teknik Informatika (Jutif), 2024)
This research underlies a deep sentimental analysis of NASA's Artemis 2 project, which aims to bring humans back to the Moon. This mission is an important milestone in NASA's efforts to build a long-term human presence on the Moon. In the context of this large and controversial project, the sentimental analysis carried out using the Recurrent Neural Network method is aimed at understanding the public view. This sentimental analysis provides a better understanding of how the public responds or perceives the Artemis 2 mission. The research questions focused on the methods of repetitive nerve tissue performance in classifying public sentiment towards the Artemis mission. The results of sentimental analysis show a strong positive trend, providing support for the continuity and sustainability of the project. From the data obtained and processed, the majority of respondents expressed a positive view of the Artemis 2 mission. Of the 49 respondents, 77.6% had a positive sentiment, 10.2% were neutral, and 12.2% were negative. The findings describe public support for the mission as a step forward in space exploration and scientific research. Nevertheless, it is important to interpret the results carefully and take into account cultural and political contextual factors. Research advice includes integrating sentimental analysis with active public participation, dealing with ethical and privacy issues, and specific analysis of specific demographic groups. The research is expected to provide in-depth insight into how people respond to space exploration, benefiting the development of sentimental analysis models, public involvement, and an understanding of social and cultural impacts.